Monitoring poly(ADP-ribosyl)glycohydrolase activity with a continuous fluorescent substrate - Drown, B; Shirai, T; Rack, J; Ahel, I; Hergenrother, P (Cell Press, 2018)
The post-translational modification (PTM) and signaling molecule poly(ADP-ribose) (PAR) has an impact on diverse biological processes. This PTM is regulated by a series of ADP-ribosyl glycohydrolases (PARG enzymes) that cleave polymers and/or liberate monomers from their protein targets. Existing methods for monitoring these hydrolases rely on detection of the natural substrate, PAR, commonly achieved via radioisotopic labeling. Here we disclose a general substrate for monitoring PARG activity, TFMU-ADPr, which directly reports on total PAR hydrolase activity via release of a fluorophore; this substrate has excellent reactivity, generality (processed by the major PARG enzymes), stability, and usability. A second substrate, TFMU-IDPr, selectively reports on PARG activity only from the enzyme ARH3. Use of these probes in whole-cell lysate experiments has revealed a mechanism by which ARH3 is inhibited by cholera toxin. TFMU-ADPr and TFMU-IDPr are versatile tools for assessing small-molecule inhibitors in vitro and probing the regulation of ADP-ribosyl catabolic enzymes.